Pengaruh PENGARUH TEKNIK PENYUNGKUPAN TERHADAP PERTUMBUHAN TUNAS SAMBUNGAN BIBIT KAKAO (Theobroma cacao L.) - Syahruni Thamrin; Junyah Leli Isnaini; Idris Risaldi (Agroplantae: Jurnal Ilmiah Terapan Budidaya dan Pengelolaan Tanaman Pertanian dan Perkebunan, 2019)
The study aimed to determine the effect of various sealing techniques on the growth of joint shoots on cocoa shoots. The studi was conducted in Tarengge Village, Wotu Subdistrict, East Luwu Regency, from February to April 2018. The study used a simple statistical analysis method with a Randomized Block Design (RBD) method, which calculated the mean (average) of each experimental treatment consists of 3 levels of treatment, namely: using the technique of pocong hood (P1), tie hood (P2), and ordinary hood (P3). The results of the experiment show that the use of various sealing techniques can affect the growth of joint buds in the top grafting of cocoa plants. The tie mask technique yielded the best results for shoot length (11.62 cm) and number of leaves (4.67 strands) on the bud buds compared to other hood techniques.